(untitled) (Journal of Informatics Education and Research, 2025)
Rapid technological advancement and automation are hallmarks of the Fourth Industrial Revolution, which calls for a workforce with high technical skills and creative problem-solving abilities. This study looks at how the 21st Century Skills Program of the Institute of Technological Resources and Entrepreneurial Development (ITRED) has affected Quezon City public high school students’ readiness for Industry 4.0. Using a mixed-methods approach that includes both quantitative assessments and qualitative interviews, this study assesses how well the curriculum has helped learners become more computer literate, robotics competent, and entrepreneurial. Students’ skill with computer programs, their comprehension and application of robotics, their readiness for Industry 4.0, and their growth as entrepreneurs are among the key characteristics that are evaluated. The program’s overall impact on the educational environment is examined, as well as student participation and attitudes toward innovation and technology. The results show that students’ technical knowledge and skills have significantly improved, and they are also showing greater interest in and involvement with technology and entrepreneurship. Additionally, the research highlights the quality of program implementation, the adequacy of resources provided, and the competency of instructors as critical factors contributing to the program’s success. The integration of ITRED’s programs into the school curriculum and the supportive role of school administrators and teachers emerged as vital elements in fostering a culture of innovation and continuous learning. This paper concludes that ITRED’s 21st Century Skills Program plays a pivotal role in preparing Quezon City students for the demands of Industry 4.0, equipping them with the necessary skills to thrive in a technologically advanced and entrepreneurial-driven economy. The study’s insights offer valuable implications for educational policymakers, curriculum developers, and educators aiming to bridge the digital divide and cultivate future innovators in the Philippines and beyond.